Immunohistochemical expression pattern of metastasis suppressors KAI1 and KISS1 in endometriosis and normal endometrium. (April 2016) - Timologou, Anna; Zafrakas, Menelaos; Grimbizis, Grigorios; Miliaras, Dimosthenis; Kotronis, Konstantinos; Stamatopoulos, Panayiotis; Tarlatzis, Basil C.
Abstract: Objective: To analyze the expression pattern of metastasis suppressors KAI1 and KISS1 in the endometrium of patients with and without endometriosis. Study design: In this pilot study, tissue samples were prospectively collected from 38 patients with endometriosis and 29 without endometriosis, undergoing operative laparoscopy in the proliferative phase of the menstrual cycle; diagnosis or absence of endometriosis was confirmed histologically. Protein expression of KAI1 and KISS1 were analyzed immunohistochemically in endometriotic lesions and the eutopic endometrium of patients with endometriosis and without endometriosis. Results: KAI1 expression was significantly decreased in the glandular eutopic endometrium of endometriosis patients as compared with that of patients without endometriosis ( p = 0.008). On the other hand, in endometriosis patients, KAI1 expression was significantly increased in the ectopic as compared with the eutopic endometrial stroma ( p = 0.021). There were no other significant differences in KAI1 expression between different groups. KISS1 expression in the ectopic glandular endometrium was significantly increased as compared with the eutopic glandular endometrium from patients with ( p = 0.004) and without endometriosis ( p = 0.008). There was no significant difference in KISS1 protein expression in the stromal endometrium between the three groups. Conclusions: KAI1 and KISS1 are implicated in the pathogenesis and maintenance of endometriosis. Future studies should investigate whether KAI1 and KISS1 could be used as markers for early and minimally invasive detection of endometriosis based on their differential protein expression pattern in the eutopic endometrium of patients with and without endometriosis.